Pengaruh Bahasa Indonesia Terhadap Penggunaan Sosial Media - Arfiryal Nashr Fillahi; Rifaldy Rachman (CV. Alim's Publishing, 2023)
The rapid development of technology and social media has impacted various sectors in society, one of which is the use of good and correct language. Nowadays, especially among teenagers, the emergence of this new trend is usually used by using cool terms in everyday speech, social media is now increasingly used by many people. The use of language can cause a polemic against the development of Indonesian language among the community. The purpose of this study is to determine the influence of social media on Indonesian language, as well as the positive and negative impacts of using Indonesian language. The research method used was an online survey using a questionnaire. This can be seen from the high level of user engagement in content written in Indonesian and also increases user confidence in interacting with others on social media. However, this study also found that the use of Indonesian on social media can affect the language style of users' writing in daily life. The implication of this study is that Indonesian can play an important role in shaping social behavior in social media and daily life.